2010
DOI: 10.1007/s00198-010-1368-1
|View full text |Cite
|
Sign up to set email alerts
|

Bisphosphonate use and risk of post-operative fracture among patients undergoing a total knee replacement for knee osteoarthritis: a propensity score analysis

Abstract: Our results suggest that BPU in primary prevention could reduce post-operative risk of fracture by 50% and by 55% in secondary prevention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 37 publications
1
8
0
2
Order By: Relevance
“…In our previous population-based cohort study, we showed a clinically significant reduction in fracture risk, of ϳ50%, after TKR in patients receiving bisphosphonates in primary prevention, and a reduction in risk of 55% in those treated in secondary prevention (36,37). This would support the fact that bisphosphonates could have a potential effect on fracture risk reduction up to 5 years after surgery among patients with lower-limb OA who undergo a joint replacement.…”
Section: Discussionsupporting
confidence: 57%
“…In our previous population-based cohort study, we showed a clinically significant reduction in fracture risk, of ϳ50%, after TKR in patients receiving bisphosphonates in primary prevention, and a reduction in risk of 55% in those treated in secondary prevention (36,37). This would support the fact that bisphosphonates could have a potential effect on fracture risk reduction up to 5 years after surgery among patients with lower-limb OA who undergo a joint replacement.…”
Section: Discussionsupporting
confidence: 57%
“…The analyses of the association between each drug use and fracture (cases vs controls) were carried out using conditional logistic regression. These models were adjusted for the corresponding propensity score in order to minimise confounding for indication [14][15][16][17][18]. As a sensitivity analysis, we carried out a further propensity-matched analysis, where users of the various antidepressants and anxiolytics and sedatives were matched 1:1 to non-users on the propensity score using a 0.2 standard deviation calliper, as recommended by some authors [19].…”
Section: Statisticsmentioning
confidence: 99%
“…[22] However, In our study, in bisphosphonate treatment group, total hip BMD was significantly increased compared to non-treatment group regardless of operation sites whether unilateral or bilateral and osteoporosis diagnosis. Prieto-Alhambra et al[23] assessed the effect of bisphosphonate use on post TKR fracture risk and reported that the HR associated with bisphosphonate therapy after TKR was 0.5 in non-fractured patients previously and 0.45 in subjects with osteoporotic and with other previous fracture. This suggested bisphosphonate treatment after TKR reduced the risk of fracture by 50-55%.…”
Section: Discussionmentioning
confidence: 99%